Wybrane zagadnienia z metodyki pracy dyrygenta z orkiestrą szkoły muzycznej I-go stopnia = Selected aspects of teaching and conducting orchestras at the primary music schools - Kaniowska, Małgorzata (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The author discusses selected issues concerning conducting orchestras at the primary music schools. The paper analyses the ways of organizing and conducting ensembles, particularly string ones. The article is an attempt to approach the key issues for the effective work with the orchestra, such as preparation of orchestral parts, repertoire or general music education.
Keywords: warsztat dyrygencki; dydaktyka; orkiestra szkolna; aranżacja; gra zespołowa; conductor skills; teaching; school orchestra; ensemble performance; arrangement